Perilaku Mekanika Balok Bambu Susun Menggunakan Penghubung Geser Baut dengan Variasi Kemiringan Baut - Noverma, Noverma; Sulistyo, Djoko; Saputra, Ashar (Jurnal Momentum ISSN 1693-752X)
Bamboo is known as building material of high tensile and flexural strength but low modulus of elasticity. It causes bamboo structure element has high deflections when load applied, and function of bamboo for building can not be utilized optimally. One of the way is to make a composed bamboo beam use bolt connector in order that deflection does not exceed the recommended limits and achieve high stiffness. The research was conducted to examine the influence of installation bolt connector on the composed bamboo beam with variety of inclination to increase shear plane of the bamboo, so that can increase strength and stiffness of the composed bamboo beam. Specimen is made single bamboo beam and two composed bamboo beam without filler and have 3 meters lenght and also with bolt connector variety of inclination (α) 90⁰, 75⁰, 60⁰, and 45⁰. Each of variety is made 3 specimens. This testing is done by two point loads at 1/3 spans on pinned-roller supported beam. To determine the mechanical properties and physical material, conducted a preliminary testing based on ISO standard. The research results showed that composed bamboo beam with the bolt connector installed in inclination 75⁰ got optimum result. Increasing percentage of composed bamboo beam load with inclination 90⁰, 75⁰ 60⁰, and 45⁰ respectively is 44%, 139%, 58%, and 22% than single bamboo beam while increasing stiffness 3 %, 6.6%, 1%, and 1.7% than stiffness of single bamboo beam. In elastic condition, ratio of theoretical load decreasing to experiment for two composed bamboo beam with assumption that the installed bamboo beam perfectly for inclination varieties of bolt connector 90⁰ , 75⁰, 60⁰, and 45⁰respectively is 0.27, 0.40, 0.20, and 0.22.while forcomposed bamboo beam with assumption that the installed bamboo beam is not perfectly (unmonolith) with bolt connector in inclination 90⁰, 75⁰, 60⁰, and 45⁰respectively is 0.95, 1.42, 0.72, and 0.78. In ultimate condition for composed bamboo beam got variety the failure pattern depend on bolt connector inclination.